Endophytic Bacteria isolated from the leaf of Langusei (Ficus minahassae Tesym. & De Vr.) and their antibacterial activities. Issue 1 (March 2020) - Tallei, T E; Linelejan, Y T; Umboh, S D; Adam, A A; Muslem; Idroes, R
Abstract: Endophytic bacteria colonizing the internal tissues of plants are being studied for its potential beneficial properties including antibacterial activity. The aims of this study were to identify the endophytic bacteria residing in the leaf of Ficus minahassae, a native plant of North Sulawesi, as well as their antibacterial activities against laboratory-adapted reference bacterial strains, Staphylococcus aureus, and Escherichia coli. The isolate identification was conducted using the 16S rRNA gene marker and the antibacterial activity test was done using a well diffusion method. A yellow-pigmented (designated as YL1) and a beige-pigmented (designated as YL2) bacteria were isolated from the internal tissue of langusei. Using the BLAST search, the isolate YL1 had a 100% identity with Brachybacterium muris, while YL2 has 99% identity with Pseudacidovorax intermedius. Ez-Taxon database confirmed that YL1 was B. muris with 99.81% similarity, while YL2 was P. intermedius with 99.80% similarity. Isolate YL2 was able to inhibit the growth of S. aureus but not E. coli. Isolate YL1 did not inhibit both reference bacteria. This study represents the first investigation of endophytic bacteria isolated from langusei leaf and their antibacterial activity.